Shifting Cost-drivers of Health Care Expenditures in Inflammatory Bowel Disease. Issue 8 (31st October 2019) - Click, Benjamin; Lopez, Rocio; Arrigain, Susana; Schold, Jesse; Regueiro, Miguel; Rizk, Maged
Abstract: Background: Inflammatory bowel diseases (IBD) are costly, chronic illnesses. Key cost-drivers of IBD health care expenditures include pharmaceuticals and unplanned care, but evolving treatment approaches have shifted these factors. We aimed to assess changes in cost of care, determine shifts in IBD cost-drivers, and examine differences by socioeconomic and insurance status over time. Methods: The Medical Expenditure Panel Survey (MEPS), a nationally representative database that collects data on health care utilization and expenditures from a nationally representative sample since 1998, was utilized. Adult subjects with IBD were identified by ICD-9 codes. To determine changes in per-patient costs or cost-drivers unique to IBD, a control population of rheumatoid arthritis (RA) subjects was generated and matched in 1:1 case to control. Total annual health care expenditures were obtained and categorized as outpatient, inpatient, emergency, or pharmacy related. Temporal cohorts from 1998 to 2015 were created to assess change over time. Per-patient expenditures were compared by disease state and temporal cohort using weighted generalized linear models. Results: A total of 641 IBD subjects were identified and matched to 641 RA individuals. From 1998 to 2015, median total annual health care expenditures nearly doubled (adjusted estimate 2.20; 95% CI, 1.6–3.0) and were 36% higher in IBD compared with RA. In IBD, pharmacy expenses increased 7% to become the largest cost-driver (44% total expenditures). Concurrently, inpatient spending in IBD decreased by 40%. There were no significant differences in the rate of change of cost-drivers in IBD compared with RA. Conclusions: Per-patient health care costs for chronic inflammatory conditions have nearly doubled over the last 20 years. Increases in pharmaceutical spending in IBD may be accompanied by reduction in inpatient care. Additional studies are needed to explore patient-, disease-, system-, and industry-level cost mitigation strategies. Abstract : Over the last 20 years, health care spending by IBD patients has nearly doubled, largely due to increasing pharmacy expenditures. Increased medication costs may be accompanied by a reduction in inpatient care.